2019
DOI: 10.1039/c9cc02524c
|View full text |Cite
|
Sign up to set email alerts
|

Highly branched poly(N-isopropyl acrylamide) functionalized with an inducer molecule suppresses quorum sensing in Chromobacterium violaceum

Abstract: Bacterial quorum sensing has been implicated in a number of pathogenic bacterial processes, such as biofilm formation, making it a crucial target for developing materials with a novel antibiotic mode of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…41 QS is relevant for the expression of bacterial virulence factors and the disruption of QS is a suitable strategy for overcoming virulence and avoiding antimicrobial resistance because QS is not necessary for survival of microbes and their inhibition does not attempt to kill but rather render them harmless or reduce the severity of their infections. 42 Quorum sensing inhibition zones were good for the polymer gels and the variation followed the same trend as for violacein inhibition. The diazaborine-based polymer microparticle PSPMA-DAZ was the most active with large inhibition zones and the results is compatible with that observed QS activity for straight chain diazaborine polymers.…”
Section: Microbial Studiesmentioning
confidence: 71%
See 2 more Smart Citations
“…41 QS is relevant for the expression of bacterial virulence factors and the disruption of QS is a suitable strategy for overcoming virulence and avoiding antimicrobial resistance because QS is not necessary for survival of microbes and their inhibition does not attempt to kill but rather render them harmless or reduce the severity of their infections. 42 Quorum sensing inhibition zones were good for the polymer gels and the variation followed the same trend as for violacein inhibition. The diazaborine-based polymer microparticle PSPMA-DAZ was the most active with large inhibition zones and the results is compatible with that observed QS activity for straight chain diazaborine polymers.…”
Section: Microbial Studiesmentioning
confidence: 71%
“…Quorum sensing in microorganisms regulates many cellular processes, which are responsible for the regulation of bacterial virulence factors, luminescence, disinfectant susceptibility, sporulation, toxin production, biofilm formation, motility and drug resistance 41 . QS is relevant for the expression of bacterial virulence factors and the disruption of QS is a suitable strategy for overcoming virulence and avoiding antimicrobial resistance because QS is not necessary for survival of microbes and their inhibition does not attempt to kill but rather render them harmless or reduce the severity of their infections 42 . Quorum sensing inhibition zones were good for the polymer gels and the variation followed the same trend as for violacein inhibition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shepherd and co-workers designed a highly branched non-biocidal polymer with its multiple end groups functionalized with AHLs. 194 Through the use of colorimetric biosensor assays, it was demonstrated that this polymer could block AHL-mediated quorum sensing in Chromobacterium violaceum. The authors explained that these polymers could show potential as antibiofilm materials owing to their quorum quenching activity, but no further antibiofilm experiments were performed in this very recent study.…”
Section: Polymers For Quorum Sensing Modulationmentioning
confidence: 99%
“…The authors explained that these polymers could show potential as antibiofilm materials owing to their quorum quenching activity, but no further antibiofilm experiments were performed in this very recent study. 194 Another interesting approach to passive quorum quenching is through the use of molecular imprinted polymer materials (MIPs). These materials are prepared through the polymerization of a monomer and crosslinker in the presence of a non-polymerizable template molecule, which is subsequently removed after curing.…”
Section: Polymers For Quorum Sensing Modulationmentioning
confidence: 99%